2022
DOI: 10.1371/journal.pone.0264619
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the use of emergency contraceptives among reproductive age women in the Kwadaso Municipality, Ghana

Abstract: Background Unintended pregnancy leads to unsafe abortion, which is one of the commonest causes of maternal deaths in developing countries including Ghana. Lots of unintended pregnancies can be avoided using emergency contraceptives (EC). Emergency contraceptives are mostly used after unprotected sexual intercourse and have a ninety-nine percent chance of preventing unintended pregnancy when taken correctly. However, unlike other modern contraceptives such as condoms, emergency contraceptives cannot prevent sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 22 publications
3
13
1
Order By: Relevance
“…21,31 However, higher levels of good attitude are seen in Kano-Nigeria, Adama and the emerging region of Ethiopia, Pretoria-South Africa, Kwadaso-Ghana and Spain. 22,26,28,29,31 Thus, non-governmental organizations, healthcare workers and social marketers should introduce strategies to counteract the negative impact of pre-existing beliefs held by young women to increase contraceptive utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,31 However, higher levels of good attitude are seen in Kano-Nigeria, Adama and the emerging region of Ethiopia, Pretoria-South Africa, Kwadaso-Ghana and Spain. 22,26,28,29,31 Thus, non-governmental organizations, healthcare workers and social marketers should introduce strategies to counteract the negative impact of pre-existing beliefs held by young women to increase contraceptive utilization.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, a lower level of good knowledge is observed among students from Selangor-Malaysia, Spain, Imo state-Nigeria, Adama and emerging regions of Ethiopia; [21][22][23][24] while a higher level of good knowledge is observed among students in Dodoma-Tanzania, Kano and Ilorin-Nigeria, Pretoria-South Africa, Kwadaso-Ghana. [25][26][27][28][29] Evidence suggests that the introduction of various educational interventions can subsequently increase the level of knowledge. 30 This study also revealed that almost half of respondents have a good attitude to contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency contraception (EC) is considered one of the effective family planning methods for reducing the risk of unintended pregnancy and its related consequences, including maternal death and disability (1) . Unintended pregnancy is a global health problem affecting women, their families and the society at large .…”
Section: Introductionmentioning
confidence: 99%
“…There are many indications for using EC as unprotected intercourse, contraceptive failure, breakage or slippage of condom, in addition to sexual assault.Moreovere, EC are safe with no serious complications or side effects. The most common side effects of EC are nausea and vomiting for oral pills while, heavy menstrual bleeding, pain and cramping or expulsion are associated with IUCD (1,2) . Emergency Contraceptive pills should be used within 72 hours of unprotected intercourse, while IUCD should be used within 5 days.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to effective parent-adolescent SRH communications are diverse and complex. In Ghana, adolescent girls particularly face several challenges in accessing SRH services (Yeboah et al, 2022). Consequently, about 50% of adolescents in Ghana are still unable to received accurate SRH information that will enable them make the right decisions and choices about their SRH (WHO, 2020).…”
Section: Introductionmentioning
confidence: 99%